Can countries bridge the gap in the quality of life? – Inheritance for Ukraine - Andriy Stavytskyy; Silviu Nate; Ganna Kharlamova; Lucian Tarnu (Journal of Business Economics and Management)
Considering that most countries exhibit substantial disparities between the rich and the poor, there is a demand for a fresh perspective on the dynamics of a country’s development and its potential for convergence. The article represents an attempt to use a comprehensive econometric framework to analyze long-term trends in people’s consumption levels across different countries of the world over the past 60 years. The obtained results indicate a paradoxical and strategically important trend: until 2008, all countries of the world demonstrated a steady growth of CPC, albeit at different rates. After 2008, there is a significant slowdown or complete absence of CPC growth in all countries. This trend indicates that the existing economic model has exhausted itself, and within its paradigm, it is impossible to stimulate new growth of CPC for the population. While some may view this as “reaching the point of well-being,” it is a point on the brink of an abyss. Regardless of political courses, the world is moving towards a new era and a new redistribution of world forces. This can explain the growth of conflicts, wars and tensions between countries. The results of the study have significant implications for understanding the sustainability and future of the world economy, as well as for the formulation of development policies and strategies at the global level.